2014
DOI: 10.1016/j.cub.2014.03.033
|View full text |Cite
|
Sign up to set email alerts
|

How the Nucleus Copes with Proteotoxic Stress

Abstract: Summary The proper folding of proteins is continuously challenged by intrinsic and extrinsic stresses, and the accumulation of toxic misfolded proteins is associated with many human diseases. Eukaryotic cells have evolved a complex network of protein quality control pathways to protect the proteome, and these pathways are specialized for each subcellular compartment. While many details have been elucidated for how the cytosol and endoplasmic reticulum counteract proteotoxic stress, relatively little is known a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 138 publications
(188 reference statements)
3
50
0
Order By: Relevance
“…In this study we chose to focus on HSP70 and melanoma, due to the enormous propensity in this tumor type for aneuploidy and mutation, both of which lead to considerable proteotoxic stress (29). Currently the role for HSP70 in melanoma is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we chose to focus on HSP70 and melanoma, due to the enormous propensity in this tumor type for aneuploidy and mutation, both of which lead to considerable proteotoxic stress (29). Currently the role for HSP70 in melanoma is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…The latter, however, would imply that these proteins are actively imported as a result of the inhibition of their original function and thus were marked for protein degradation. Indeed, recent studies provide compelling evidence that cytosolic misfolded proteins are actively imported into the nucleus for proteasomal degradation (Prasad et al 2010;Park et al 2013;Shibata and Morimoto 2014). Having found that the major fraction of 20S proteasomes is located in nuclei of both placebo-and propiverinetreated F344 rats and that the BioGRID interaction database provides evidence that DAAO interacts with KLHL42, a substrate-specific adapter of an E3 ubiquitin-protein ligase, 1 we wanted to demonstrate that proteins, e.g., DAAO and catalase are imported into the nucleus for proteasomal degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Hence they heavily depend on their innate "proteotoxic surveillance" provided by ubiquitous molecular chaperones, the heat shock proteins. Chaperones are necessary to regulate various cellular signaling processes and prevent deleterious age-associated accumulation of protein aggregates (11,12). Although a high degree of complex aggregates is found in the post-mitotic neurons with age-related neurodegenerative diseases (Alzheimer, Parkinson, and Huntington diseases, etc.…”
Section: Waf1mentioning
confidence: 99%